Does person-centred care improve outcomes for musicians fitted with hearing protectors?. (30th October 2020) - McGinnity, Siobhan; Beach, Elizabeth Francis; Cowan, Robert; Mulder, Johannes; Power, Dominic; Barr, Caitlin
Abstract: Objective: To reduce the risk of hearing injury, musicians are often recommended custom-made musicians' hearing protectors (MHP). Studies report benefits of use however, many still report challenges leading to relatively low uptake and inconsistent usage. Person-centred approaches to health have been shown to improve patient outcomes, and these principles may be translatable to musicians' hearing care. The aim was to investigate if use of, and satisfaction with, MHP is influenced by the treatment delivered to musicians by audiologists. Design: Participants were randomly allocated to one of four conditions that varied in extent of person-centred care. Study sample: Forty-two musicians with an interest in purchasing MHP were recruited. Results: Satisfaction with MHP was high overall and users reported a reduction in incidence of tinnitus. Participants reported few issues related to sound quality, however insertion difficulty was the main problem reported. Only one musician self-identified the need for alterations to their MHP. Conclusions: Adoption of person-centred approaches to MHP was not found to increase likelihood of use, however, satisfaction was high across all conditions. Most often, the need for MHP alterations were clinician-identified during fitting appointments or follow-up contact, underscoring the importance of including these components when providing audiological services to musicians.